2016
DOI: 10.14444/3019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Bundled Payment System on Resource Utilization During Spine Surgery

Abstract: BackgroundIn a bundled payment system, a single payment covers all costs associated with a single episode of care. Spine surgery may be well suited for bundled payments because of clearly defined episodes of care, but the impact on current practice has not been studied. We sought to examine how a theoretical bundled payment strategy with financial disincentives to resource utilization would impact practice patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…49,50 Implementation of similar strategies may be on the horizon for the increasing number of ASC spinal surgery procedures, which makes understanding factors contributing to postoperative complications and readmissions crucial in the overall design of a value-based outpatient spine care program. 22 Although a precise cost-benefit analysis of the outpatient transforaminal decompression versus traditional microdiscectomy was beyond the scope of this study, it is obvious that performing low-cost/ low-risk spinal endoscopy in an ASC realizes immense cost savings when comparing lower complication rates and fewer postoperative ER visits and hospital readmissions than reported with other spinal surgeries. It has been estimated that inadequate management of care transitions related to avoidable complications and unnecessary hospital readmissions was responsible for $25 to $45 billion in wasteful spending in 2011 alone.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…49,50 Implementation of similar strategies may be on the horizon for the increasing number of ASC spinal surgery procedures, which makes understanding factors contributing to postoperative complications and readmissions crucial in the overall design of a value-based outpatient spine care program. 22 Although a precise cost-benefit analysis of the outpatient transforaminal decompression versus traditional microdiscectomy was beyond the scope of this study, it is obvious that performing low-cost/ low-risk spinal endoscopy in an ASC realizes immense cost savings when comparing lower complication rates and fewer postoperative ER visits and hospital readmissions than reported with other spinal surgeries. It has been estimated that inadequate management of care transitions related to avoidable complications and unnecessary hospital readmissions was responsible for $25 to $45 billion in wasteful spending in 2011 alone.…”
Section: Discussionmentioning
confidence: 98%
“…Postoperative recovery is further expedited with the use of spinal endoscopes that traverse a smaller surgical access corridor with their working cannula. [17][18][19][20][21] The combination of these developments has facilitated a substantial increase in the types of procedures being conducted in an ambulatory surgery center (ASC), 14,15 a trend that is welcomed by more patients because of convenience and less burdensome treatments, and, moreover, is motivated by recent coverage and bundled payment guidelines 22 of insurance providers and governmental institutions and review boards intended to help stem the rise of health care cost. This observation is corroborated not only by the recent substantial increase of current procedural terminology (CPT) codes for spinal surgeries, including fusions eligible for payment in ASCs, but also by the addition of new endoscopic decompression CPT codes for spinal surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] While BPCI have not yet been widely adopted for ACDF, there has recently been significant interest in the potential implications of the adoption of alternative payment methods in spine surgery. [11][12][13][14][15] A survey of predominantly academic-affiliated organizations employing over 110 spine surgeons found reservations and concerns, but an increased interest in the use of bundled payments for spine surgery reimbursement. 15 Clearly, in order for bundled payments to be effective in controlling cost for cervical spine surgery, proper risk stratification is necessary.…”
Section: Introductionmentioning
confidence: 99%
“… 24 A survey of 43 spine surgeons showed that bundled care implementation would alter decision making such as more conservative use of allograft rather than autograft, routine neuromonitoring, and rigid post-operative bracing. 25 As payment models shift toward bundled payments, it is important to explore strategies that will promote a smooth transition as well as cost efficiency and outcome-based care.…”
Section: Strategies For Implementationmentioning
confidence: 99%